Digital Transformation in Marriage Administration: Analysis of The Implementation of the ELSIMIL Application in Marriage Registration - Syatta, Indy Mafiiqo (Nursyam Centre, 2024)
The development of information technology has changed many aspects of life, including government administration, for example, the application